2007
DOI: 10.1080/00103620701759178
|View full text |Cite
|
Sign up to set email alerts
|

Critical Limit of Extractable Phosphorous in a Gleysol for Rice Production in the Senegal River Valley of West Africa

Abstract: Soil-test correlation and calibration, a useful tool for fertilizer recommendations, has been little used in West Africa. Soils from a long-term fertility experiment have been used to study the relationship between rice yields and soil extractable phosphorus (P) with Bray 1 and Olsen methods. The Cate and Nelson graphical method was used for critical limits of soil P determination. The critical limits of soil extractable P at 95% relative grain yield were 9 mg P for the Bray 1P and 17 mg P kg 21 for Olsen P. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 5 publications
3
20
0
1
Order By: Relevance
“…The LTFEs revealed that soil extractable P increased from 3.8 to 6.8 mg P kg -1 at Fanaye) and from 4.9 to 9.7 mg P ha -1 at Ndiaye with seasonal applications of the recommended dose of NPK fertilizer. Soil-P data from this research were on averagely very close to the critical limit (9 mg P kg -1 ) for rice production (Bado et al, 2007) and were similar to those obtained in the LTFE with the seasonal application of 26 kg P ha -1 after 18 years of cultivation.…”
Section: Agricultural Sciencesupporting
confidence: 57%
See 3 more Smart Citations
“…The LTFEs revealed that soil extractable P increased from 3.8 to 6.8 mg P kg -1 at Fanaye) and from 4.9 to 9.7 mg P ha -1 at Ndiaye with seasonal applications of the recommended dose of NPK fertilizer. Soil-P data from this research were on averagely very close to the critical limit (9 mg P kg -1 ) for rice production (Bado et al, 2007) and were similar to those obtained in the LTFE with the seasonal application of 26 kg P ha -1 after 18 years of cultivation.…”
Section: Agricultural Sciencesupporting
confidence: 57%
“…P becomes a limiting factor for increasing rice yield when the soil supplies less than 9 mg P kg -1 and P fertilizer should be applied under such conditions in order to increase rice yields. Above this value, responses to P fertilizer applications are not expected (Bado et al, 2007). Data of soil extractable P should be used to confirm the necessity to apply P fertilizers to overcome this limiting factor.…”
Section: Agricultural Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…The reliable nutrient status of farmers' fields' true will only be revealed through chemical soil testing during a particular growing season. The most widely used available soil P test is Bray II (Bray and Kurtz, 1945) on acidic soils (Bado et al, 2008). Instead of simple individual soil tests, soil calibrations of the relationship between soil test and yields of a specific plant are needed for fertilizer recommendation.…”
Section: Introductionmentioning
confidence: 99%